Dinamika Stres Akademik, Dukungan Sosial, dan Agresivitas pada Siswa Sekolah Menengah Kejuruan - Yafia Nada Aubertha; Tri Na’imah; Herdian; Fatin Rohmah Nur Wahidah (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2025)
Academic pressure and social demands can trigger maladaptive behaviors, one of which is aggressiveness. Academic stress and low social support are suspected to contribute to the increasing tendency for aggressiveness among students. This study aims to examine academic stress and social support on the tendency for aggressiveness among 11th-grade students at SMK Ma’arif NU 1 Ajibarang. This research used a quantitative approach with simple random sampling. The sample consisted of 269 students from a total population of 898. The instruments used were the Aggression Questionnaire (AQ), the Student-Life Stress Inventory (SLSI), and the Multidimensional Scale of Perceived Social Support (MSPSS). The results showed that academic stress had a significant influence on the tendency for aggressiveness, with an F value of 222.833 and p = 0.000 (p < 0.05), contributing 45.3%. Social support also had a significant influence with F = 5.987 and p = 0.015 (p < 0.05), contributing 1.8%. Together, academic stress and social support contributed 45.1% with F = 111.167 and p = 0.000 (p < 0.05).